Better behaviour : ages 10-12 - McGrath, Helen (London : A & C Black, 2000)
Disruptive behaviour has a severe impact on both teachers' morale and pupils' levels of attainment - and tackling this problem is an enormous challenge for primary schools. A recent study commissioned by the NUT found that more than 80 per cent of teachers in schools of all types in rural, urban and inner city areas say that pupil behaviour has deteriorated during their time of teaching. Teachers are looking for effective solutions.
"photocopiable activities"--cover.
Keywords: Educational psychology